2021
DOI: 10.3389/fpls.2021.700479
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Enhanced Resistance to Botrytis cinerea in Strawberry Fruits (But Not Leaves) Is Associated With Changes in the Rhizosphere Microbiome

Abstract: Biochar has been reported to play a positive role in disease suppression against airborne pathogens in plants. The mechanisms behind this positive trait are not well-understood. In this study, we hypothesized that the attraction of plant growth-promoting rhizobacteria (PGPR) or fungi (PGPF) underlies the mechanism of biochar in plant protection. The attraction of PGPR and PGPF may either activate the innate immune system of plants or help the plants with nutrient uptake. We studied the effect of biochar in pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 69 publications
(142 reference statements)
0
18
0
Order By: Relevance
“…Biochar amendment in soil/substrate has shown positive effects on plant defense against different pathogens, however, limited data is available for insect pests (De Tender et al, 2021). The spread of T. absoluta in mainland China (Zhang et al, 2021) calls for the exploration of possible strategies to reduce tomato crop losses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar amendment in soil/substrate has shown positive effects on plant defense against different pathogens, however, limited data is available for insect pests (De Tender et al, 2021). The spread of T. absoluta in mainland China (Zhang et al, 2021) calls for the exploration of possible strategies to reduce tomato crop losses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of transcriptome sequencing and metabolome profiling can help us identify the key metabolites and genes that are accumulated or expressed, respectively, in tomato plants grown in soil amended with bamboo charcoal. A similar strategy has helped researchers identify genes and associated pathways such as protein processing, plant-pathogen interaction, photosynthesis, and signaling in response to different biotic stresses e.g., in pepper against Fusarium wild (Zhu et al, 2021), in oat against oat-stem-rust (Li et al, 2022), and in strawberry fruits against Botrytis cinerea (De Tender et al, 2021). In this study, we used a combined metabolome profiling and transcriptome sequencing approach to understand the key changes in the accumulated metabolites and respective changes in gene expression in leaves of tomato plants grown in coconut bran amended with bamboo charcoal.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the Wasatch genotype demonstrated relatively higher mycorrhizal colonization compared to controls, which likely underlie some of the observed genotype x AMF interactive effects. Previous studies indicate that plant genotypes, including different strawberry cultivars, can show variable responsiveness to different species or strains of AMF ( Chávez and Ferrera-Cerrato, 1990 ; Vestberg, 1992 ; Estaún et al., 2010 ; Sinclair et al., 2014 ), and recent research highlights the importance of fungal diversity ( De Tender et al., 2021 ; Frew et al., 2022 ). Because we did not identify fungal species when measuring root colonization, there is uncertainty about AMF community composition and the extent to which our inoculation contributed to higher colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biochar helps to improve the population of soil beneficial microbial communities which in turn help in the suppression of soil-borne plant pathogens. Tender et al (2021) reported the attraction of plant beneficial rhizobacteria and fungi as the mechanism behind the role of biochar in plant disease suppression, based on the studies using the strawberry -Botrytis cinerea plant pathogen system. Botrytis cinerea is a pathogen that affects both fruits and leaves of strawberry plants.…”
Section: Biochar In Plant Disease Managementmentioning
confidence: 99%